Model of the Indonesian Legal System - Dian Ekawati (Jurnal Kewarganegaraan, 2023)
Abstract This research aims to analyze the legal system of Indonesia with a focus on the model of customary law, written law, and the judicial structure. The research method employed is normative research with a library research approach. In the analysis of library research, the researcher collected and analyzed various relevant legal sources, including laws, constitutions, court decisions, and related legal literature. The researcher also compared the legal systems of Indonesia and other countries, particularly Malaysia, to gain a better understanding of the differences and similarities in their legal systems. The research findings indicate that the legal system of Indonesia possesses distinct characteristics and differences. One significant aspect is the recognition of the role of customary law within its legal system. Customary law plays a vital role in regulating social relationships, customary practices, and dispute resolution within the society. This sets Indonesia apart from many other countries that rely more heavily on written law. Indonesia places a strong emphasis on written law, with the Constitution serving as the primary source of law. The existence of written law underscores the importance of legal certainty within the Indonesian legal system. Additionally, Indonesia incorporates elements of Islamic law and international law, reflecting efforts to integrate diverse legal sources into the national legal system. In terms of the judicial structure, Indonesia has a similar hierarchy of courts as many other countries, including trial courts, appellate courts, and a court of cassation. This judicial system provides essential mechanisms to ensure justice and legal certainty for individuals. Keywords: Indonesian Legal System, Model of Customary Law, Model of Written Law